A self-defense redox mediator for efficient lithium–O2 batteries. Issue 3 (5th January 2016) - Zhang, Tao; Liao, Kaiming; He, Ping; Zhou, Haoshen
Abstract : InI3, a self-defense redox mediator, can form a pre-deposited indium layer to resist the synchronous attack on a Li anode by the soluble I3 −, and hence can suppress the shuttle effect in lithium–O2 batteries. Abstract : Redox mediators (RMs) have become focal points in rechargeable Li–O2 battery research to reduce overpotentials in oxygen evolution (charge) reactions. In this study, we found an evidence for the shuttle effect arising in dimethyl sulfoxide (DMSO) with a LiI RM through the visual observation of the diffusion of soluble I3 − towards a Li anode where it reacted chemically to produce LiI, which can be only partly dissolved, leading to the loss of both the RM and electrical energy efficiency. Therefore, we proposed a self-defense redox mediator (SDRM) of InI3 to counter this problem. During charging, the In 3+ is reduced electrochemically on the Li anode prior to Li +, forming a much stable indium layer to resist the synchronous attack by the soluble I3 − . The pre-deposited indium layer can also reduce the growth of dendrites from the Li anode surface. As a result, the electrical energy efficiency and the cycling performance of the Li–O2 cells were improved significantly.